The local cyclicity problem: Melnikov method using Lyapunov constants - Gouveia, Luiz F. S. [UNESP]; Torregrosa, Joan (Cambridge University Press (CUP), 2022)
In 1991, Chicone and Jacobs showed the equivalence between the computation of the firstorder Taylor developments of the Lyapunov constants and the developments of the first Melnikov function near a non-degenerate monodromic equilibrium point, in the study of limit cycles of small-amplitude bifurcating from a quadratic centre. We show that their proof is also valid for polynomial vector fields of any degree. This equivalence is used to provide a new lower bound for the local cyclicity of degree six polynomial vector fields, soM(6) ≥ 44. Moreover, we extend this equivalence to the piecewise polynomial class. Finally, we prove that Mcp(4) ≥ 43 and Mcp(5) ≥ 65.
Keywords: local cyclicity; Lyapunov constants; Melnikov theory